Detection DETEKSI DAN IDENTIFIKASI KAPANG PADA PROSES BIODETERIORASI ARSIP FOTO MEMORY OF THE WORLD (MOW) RESTORASI CANDI BOROBUDUR - Imam Riadi; Bernadetta Octavia; Mohamad Habibi (Balai Konservasi Borobudur Magelang, 2021)
ABSTRACT This study aims to identify the genus of mold in the biodeterioration process of the photo archive of Memory of the World (MoW) restoration of Borobudur Temple and the potential for the enzymatic activity of these molds. The type of research method chosen is descriptive qualitative. Starting with survey sampling and sampling. Inoculation of fungi using the streak method on PDA medium. Mold identification based on macroscopic and microscopic observations of fungi. The results of characterization were then identified using the matching profile method using the mold identification reference book. The identification results resulted in six genera of contaminant molds in the biodeterioration of the MoW photo archive of the Borobudur Temple restoration. The genera identified included: Acremonium (69.66 %%), Penicillium (14.59%), Aspergillus (3.36%), Culvularia (2.24%) Fusarium (1.12%), and Pleurostomophora (1.12%) and some sterile mycelia. The types of biodeterioration in the photo collection include mold growth, discolored spots, peeling off layers, and damage to the substrate in the photo. Based on literature search, all mold genera found as the cause of biodeterioration has the potential to have proteinase, gelatinase, and cellulase enzymes. Keywords: Biodeterioration; Mold; Photograph; Memory of the World; Borobudur Temple